A preliminary investigation of the definition and components of computational thinking in the Malaysian education landscape: from educational technology experts' perspective - Abdul Hamed, Ahmad Sarji; Wong, Su Luan; Abdul Rani, Mohd Zariat; Md Khambari, Mas Nida; Abd Rahim, Nur Aira; Khalid, Fariza; Moses, Priscilla (Asia-Pacific Society for Computers in Education, 2024)
This qualitative study explores the definition and essential components of computational thinking (CT) within the Malaysian educational context. Through semi- structured interviews with educational technology experts, the research delves into the nuanced understanding of CT, considering its adaptation to the local educational landscape and its broader applicability beyond technical skills. The findings reveal that CT in Malaysia is defined as a problem-solving methodology emphasizing inclusivity and thinking, as guided by the Malaysian Ministry of Education (MOE). Essential of CT identified by experts align with MOE's framework and encompass abstraction, decomposition, pattern recognition, algorithms, logical reasoning, and evaluation. This approach equips students with skills for a computational world and strengthens their critical thinking. The study concludes that integrating CT by focusing on these key skills can enhance students' problem-solving abilities and support national progress. Limitations include the study's focus on educational technology experts. potentially excluding broader educator perspectives, and variations in CT adaptation across regions. Future research should include diverse educator viewpoints and longitudinal studies to assess CT instruction's long-term impact and effectiveness.